The potentials of an integrated ultrasonic membrane anaerobic system, iumas for pome treatment - Hamid Nour, Abdurahman; Radhwa, Muhammad Farid (2021)
With the increasing energy crisis and the drive to reduce CO2 emissions, universities and industries are challenged to find new technologies in order to reduce energy consumption, to meet legal requirements on emissions, and for cost reduction and increased quality. The direct discharge of Palm Oil Mill Effluent, POME wastewater causes serious environmental pollution due to its high chemical oxygen demand (COD), Total suspended solids (TSS) and biochemical oxygen demand (BOD). Traditional ways for POME wastewater treatment have both economical and environmental disadvantages. In this study, ultrasonic assisted-membrane anaerobic system (UMAS) was used as an alternative, cost effective method for treating POME wastewater (to avoid membrane fouling).